2005
DOI: 10.1259/dmfr/12901010
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound crack detection in a simulated human tooth

Abstract: A unique ultrasound dental crack detection system using a novel transducer; a novel coupling agent; and customized electronic and digital signal processing (DSP) algorithms has been validated in a simulated tooth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
63
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 8 publications
0
63
0
Order By: Relevance
“…Ultrasound has previously been investigated as a complement to dental radiography as a tool to detect caries, fractures, and debonded restorations. [1][2][3][4] However, progress in dental ultrasound has been limited by a number of factors. The high acoustic impedances of dental tissues result in surface losses that limit the use of commercially available medical transducers and acoustic scanning gels since these are not acoustically matched to teeth.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound has previously been investigated as a complement to dental radiography as a tool to detect caries, fractures, and debonded restorations. [1][2][3][4] However, progress in dental ultrasound has been limited by a number of factors. The high acoustic impedances of dental tissues result in surface losses that limit the use of commercially available medical transducers and acoustic scanning gels since these are not acoustically matched to teeth.…”
Section: Introductionmentioning
confidence: 99%
“…9 VRFs can generally be diagnosed only by observation of a fracture line with or without a surgical method. [10][11][12] It would be advantageous to find more efficient methods for diagnosing VRF pre-operatively to avoid the cost and effort of unnecessary apical root resections. 13 CBCT has become useful in various fields of dentistry, including endodontic surgery, and also in various endodontic diagnostic procedures, including the assessment of root fractures.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the bracket removal procedure is related with the EMCs increase and formation of new EMCs [9][10][11][12][13] . Various methods, such as transillumination, staining, ultrasound, or optical coherence tomography (OCT) have been described in the literature for EMCs detection [14][15][16][17] . Some of these techniques (e.g., transillumination and staining) can be applied directly intraorally for EMCs visual examination and diagnosis 14) .…”
Section: Introductionmentioning
confidence: 99%
“…There are several laboratory techniques (scanning electron microscopy (SEM), stereomicroscopy, confocal optical profilometry (COP), three dimensional (3D) scanning methods) that can be employed to measure volumetric enamel loss, actual depth of enamel removed, or perform spot or line measurements of EMCs parameters 1,11,[15][16][17][18][19][20][21] . The most often methods used and described in the literature, their advantages and disadvantages in terms of quantitative EMCs characteristics examination are presented in Table 1 15 -17,22-24) .…”
Section: Introductionmentioning
confidence: 99%